Diverse Lenabasum pathway activation in dermatomyositis patients’ blood - Nilesh Kodali; DeAnna Diaz; Rohan Dhiman; Thomas Vazquez; Rui Feng; Jay Patel; Joshua Dan; Grant Sprow; Julianne Kleitsch; Meena Sharma; Muhammad Bashir; Victoria P. Werth (Scientific Reports)
Abstract Lenabasum, a non-psychoactive cannabinoid type-2 receptor (CB2R) agonist, has shown promise in reducing cutaneous disease in Dermatomyositis (DM) patients. Lenabasum activates two distinct receptors: CB2R and the nuclear peroxisome proliferator-activated receptor-γ (PPARγ). Our goal was to investigate the dominant mechanism of action leading to pathogenic IFNβ reduction by lenabasum (through CB2R or PPARγ) across leukocytes. We utilized whole blood leukocytes from 14 DM patients and grouped patients as in vitro responders or non-responders. We stimulated leukocytes in vitro in the presence of CB2R and PPARγ inhibitors and lenabasum. Intracellular and extracellular marker expression was analyzed by flow cytometry. CD4+ T (p < 0.05), monocyte-derived dendritic cells (p = 0.06), and intermediate monocytes (iMs) (p < 0.05) activate a CB2R-mediated lenabasum pathway in responders. Responder B cells (p < 0.01), CD8+ T cells (p < 0.01), and non-classical monocytes (p = 0.06) activate a co-dependent CB2R/PPARγ-mediated lenabasum pathway. Lenabasum can independently activate CB2R or PPARγ in myeloid dendritic cells (p < 0.05). Responder plasmacytoid dendritic cells (p < 0.05) and classical monocytes (p < 0.01) activate a PPARγ-mediated lenabasum pathway. CB2R was increased in certain responder CB2R-mediated cell populations compared to non-responders. Lenabasum elevated cyclooxygenase-2 or 15-lipoxygenase-1 levels in all responder CB2R-mediated cell populations except iMs. Baseline cell-to-cell CB2R/PPARγ testing could be useful to select ideal lenabasum candidates. Trial Registration: Registered at ClinicalTrials.gov (Identifier: NCT03813160) on 2019–01-23. Sponsored by Corbus Pharmaceuticals Inc.